Pedagogical Professional Development of Medical Teachers: The Experience of NOVA Medical School / Universidade Nova de Lisboa - NOVA Medical School|Faculdade de Ciências Médicas (NMS|FCM) (2018)
Introduction: To be a college teacher requires a permanent effort in developing specific competencies, namely in the pedagogical domain. This paper aims both to describe the pedagogical professional development program offered by the Medical Education Office of NOVA Medical School of Universidade Nova de Lisboa and to analyse its role in the enhancement of reflection around curriculum and teaching practice. Material and Methods: Description of the pedagogical programme offered between 2010 and 2016. We focused the analysis on different kinds of data-opinions of the participants in the training programme (questionnaire before and after the training); pedagogical products elaborated by the participants in the programme-design of lessons, modules or curricular units; questionnaire sent in 2016 to NOVA Medical School teachers responsible for the curricular units, about the contribution of their disciplines to the accomplishment of the core learning outcomes of the NOVA Medical School medical graduates. Results: The pedagogical training needs identified by the teachers focused mainly on improving practice, critically analysing the curriculum and sharing experiences. Globally the training programme was deeply appreciated and considered very good by 97% of the participants. The lesson plans delivered showed that the teachers were able to integrate and apply the concepts developed during the training. The answers from the 46 faculty responsible for the curricular units (the majority of them had attended the Medical Education Office training programme) highlighted their capacity to critically approach content and pedagogical strategies within their disciplines as well as their contribution to the main goals of the medical curriculum. Discussion: The results underlined the importance of a pedagogical training focused on the critical analysis of curriculum and pedagogical practice. On the other hand, the pedagogical products analyzed revealed great mastery by teachers of the content and pedagogical strategies present in the curricula of their respective curricular units, as well as their alignment with the general objectives of the Mestrado Integrado em Medicina. Conclusion: In line with the literature of the specialty, pedagogical training in Higher Education, rather than aiming at the mere acquisition of techniques, should, above all, give priority to spaces for joint reflection on the curriculum and on the pedagogical options of teachers. © Ordem dos Médicos 2017.